STRATEGI PEMASARAN DAN DIGITALISASI PADA USAHA GROSIR LOKASI TIDAK STRATEGIS : WARUNG BUDE - M. Royhan Safdan Muzaki Harahap; Vicky Febima Andrerico; Zainarti Zainarti (Adisam Publisher, 2025)
Wholesale businesses play an important role in the distribution of goods, but not all wholesalers are in strategic locations. Some of them operate in hidden places such as alleys, which makes it difficult for consumers to access and reduces business visibility. This condition has an impact on decreasing the number of customers, limited market reach, and less than optimal business growth. In facing these challenges, the right marketing strategy and adoption of digitalization are potential solutions to increase competitiveness. Digitalization through social media, e-commerce platforms, and digital payments can help wholesale businesses reach a wider market, introduce products eflectively, and increase operational efficiency. Unfortunately, many wholesale business actors in non-strategic locations still rely on conventional methods and have not optimized digital potential. Therefore, research is needed to explore the right marketing and digitalization strategies for wholesale businesses in less strategic locations so that they can survive and thrive in this era of modern competition.